Similar impressions? Anglo-American relations and South Asia, autumn 1971. (3rd April 2018) - Riley, Dave
Abstract : Despite divergences of policy over South Asia in autumn 1971, Heath and Nixon's communications focused upon areas of agreement. An unwillingness to confront disagreements over policy subsequently fostered misunderstandings between the two allies as both lent tacit support to opposite sides of a hot war in South Asia just weeks later. Nonetheless, Heath's desire to improve the tone of Anglo-American relations in the autumn of 1971 provides a further challenge to the commonly held assertion that his desire to enter the EC led him to shun an amiable relations with the US.